AN ANALYSIS OF THE LINGUISTIC COMPETENCE OF MORPHOLOGY TEACHING ON YOUTUBE VIDEO SERIES - Lailatul Maya; Ratna Dewanti; Muchlas Suseno (Jurnal Bahasa Lingua Scientia, 2023)
Linguistic competence has had a significant influence on English language teaching. Linguistic competence is largely concerned with a notion shared by language teachers and learners when using language knowledge in real performance. English teachers are expected to have this competency. The present study aimed to examine linguistic competence in morphology teaching, which was demonstrated by an English teacher. The morphology teaching was sourced from a series of YouTube videos which were broadcast by a teacher on a Youtube channel. This study was carried out by analyzing the linguistic competence of the teacher in each video by analogizing the teacher’s knowledge with the theory from the linguistics book written by some experts. The selected books which were used to analyze were: “How English Works, A Linguistic Introduction” (Curzan & Adams, 2012); “Linguistics, An Introduction” (Radford et al., 2009); and “Contemporary Linguistic Analysis, An Introduction” (O’Grady & Archibald, 2016). The study’s findings revealed that the teacher had sufficient linguistic competence while delivering the course. The findings also assisted in recognizing that linguistic competence is a significant part of the analysis in terms of how a teacher may remain competent while providing the course. In short, linguistics is considered valuable because it may increase teacher’s awareness of language, making the teacher more competent and, hence, a better language teacher.